Dynamic uneven clustering protocol for efficient energy management in EH-WSNs. (2022) - Puviarasu, A; Balaji, M; Thirukkumaran, R; Siva Kumar, A; Premkumar, M
Abstract: In recent days, the Energy Harvesting Wireless Sensor Networks (EH-WSNs) are designed to reduce the amount of energy used by sensors. In order to reduce the energy consumption of these components, the new algorithm namely Dynamic Uneven Clustering Protocol (DUCP) is proposed that will automatically cluster the harvested energy sources. The protocol aims to improve the energy management of a cluster head (CH) by selecting better performing nodes. Since rechargeable batteries have a limited capacity, a dynamic transmit power control strategy is devised for both CHs and cluster members during the data gathering process to improve collected energy consumption. A number of tests are conducted to verify the performance of the proposed DUCP algorithm, and the results demonstrate that the DUCP technique effectively utilizes energy and outperforms its rivals.